Lower well‐being of young Australian adults with self‐reported disability reflects their poorer living conditions rather than health issues - Eric Emerson; Gwynnyth Llewellyn; Anne Honey; Maina Kariuki (Elsevier, 2012)
Abstract Objective: To determine the extent to which the lower well‐being of young Australians with disabilities could be accounted for by increased rates of exposure to adversity and reduced access to personal, economic, social and community resources. Methods: Secondary analysis of data extracted from Waves 1 (2001) to 8 (2008) of the annual longitudinal survey of Household Income and Labour Dynamics in Australia. Results: Self‐reported disability was associated with significantly lower scores on all indicators of psychological well‐being. However, people self‐reporting disability were more likely to be exposed to adversity and less likely to have access to a range of personal, economic, material, social and community resources. When these between‐group differences in social context were controlled for, the between‐group differences in psychological well‐being were largely eliminated. Conclusion: Our results suggest that, among younger adults in Australia, the association between disability and lower psychological well‐being largely reflects their increased risk of exposure to adversity and reduced access to resources, rather than the presence of health conditions or impairments per se. Implications: Public health interventions aimed at improving the well‐being of young adults with a disability need to address the predominantly social determinants of well‐being in this group.